GAMBARAN BUDAYA KESELAMATAN PASIEN PADA PETUGAS PUSKESMAS DI KOTA DENPASAR - Artini, Ni Wayan Noni; Nopiyani, Ni Made Sri (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT The government is trying to improve the quality of Primary Health Care (PHC) services, one of which is through the implementation of patient safety. However, there are still patient safety incidents in PHC. Therefore, it is important to assess patient safety culture as a basis for patient safety improvement efforts. This study aims to determine the description of patient safety culture at PHC officers in Denpasar City. This study used descriptive quantitative method with cross sectional design. The sample came from 100 health workers. Data collection used HSOPSC 2.0 questionnaire. Data analysis used descriptive analysis and analysis of different proportions. The results showed that the description of patient safety culture among PHC officers in Denpasar City was in the strong category (84%). Almost all dimensions are in the strong category, but 2 dimensions are in the moderate category, namely the dimension of response to errors and the dimension of staffing response and work speed. There is a significant difference in the proportion of patient safety culture based on the characteristics of age and length of service. Meanwhile, there is no significant difference in patient safety culture based on gender, latest education and accreditation status of PHC. PHC and the Health Office of Denpasar City need to make continuous improvements to improve the implementation of patient safety culture in officers. Keywords:  Patient Safety Culture, Primary Health Care Officer